Importance of The Medical History in The Diagnosis of Hypersensitivity Pneumonitis: A Case Report - Ecin, Seval Müzeyyen; Sandal, Abdulsamet; Koyuncu, Adem; Öz, Şerife Gül (Acta Medica, 2020)
Introduction: Hypersensitivity pneumonitis, most frequent types are those related to farming and bird breeding. In this paper, a patient with occupational exposure to metal dusts and welding fumes but diagnosed with HP thanks to the guidance of detailed anamnesis revealing inhalational exposure to pigeon antigens both at home and in workplace Case: 32-year-old male. He applied with shortness of breath, dry cough. He has been working production of kitchen equipment made from stainless steel. When environmental exposures questioned, he declared that he bred up to ten pigeons at the basement of his house and up to fifteen pigeons at a coop next to workplace building. Spirometry revealed restrictive pattern. In patient’s chest X-ray, bilateral increased reticular densities were observed. Computed tomography of thorax revealed radiological findings supporting subacute hypersensitivity pneumonitis such as bilateral diffuse millimetric centrilobular ground-glass nodules which are coalescing in some areas, mosaic perfusion and air trapping in basal areas. Bronchoalveolar lavage cytology revealed percentages of lymphocytes as 85%. Discussion: Detailed anamnesis revealing environmental and occupational inhalational exposures guides the physician in diagnosis of HP. After initial suspicion, supporting laboratory and radiologic findings confirm the diagnosis to provide appropriate management.